2016
DOI: 10.1111/trf.13819
|View full text |Cite
|
Sign up to set email alerts
|

Detection of different categories of hepatitis B virus (HBV) infection in a multi‐regional study comparing the clinical sensitivity of hepatitis B surface antigen and HBV‐DNA testing

Abstract: ID-NAT and serology are complementary in detecting HBV infection in first-time donors, but HBV-DNA is superior to HBsAg detection in repeat donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 21 publications
8
80
1
Order By: Relevance
“…The very low viral load of HBV DNA may result in the false‐negative results of HBV DNA testing. Similar result was reported by Lelie and coworkers that HBV DNA–positive donations with lower viral load were detectable because of a strategy of replicate Ultrio and dHBV testing on samples taken from the fresh‐frozen plasma sample. This study indicated the need to improve the HBV DNA NAT assays or adopt repeat HBV DNA testing to increase the rate of detection of OBI donations so as to decrease transfusion transmitted HBV infection by OBI donations.…”
Section: Discussioncontrasting
confidence: 70%
“…The very low viral load of HBV DNA may result in the false‐negative results of HBV DNA testing. Similar result was reported by Lelie and coworkers that HBV DNA–positive donations with lower viral load were detectable because of a strategy of replicate Ultrio and dHBV testing on samples taken from the fresh‐frozen plasma sample. This study indicated the need to improve the HBV DNA NAT assays or adopt repeat HBV DNA testing to increase the rate of detection of OBI donations so as to decrease transfusion transmitted HBV infection by OBI donations.…”
Section: Discussioncontrasting
confidence: 70%
“…When using a more sensitive NAT, with 50 and 95% LODs at 2.2 and 21.4 copies/mL, δ detected is estimated to be 0.70. Finally, the estimate for δ aHBsNeg was found to be approximately 0.50 in a large multiregional study …”
Section: Resultsmentioning
confidence: 88%
“…Among blood donors in recent years, the incidence of OBI has varied with the prevalence of HBV and public health conditions. Specifically, the OBI incidence was 1:27 (19 of 507 donors) in Nigeria, 1:450 (8 of 3600 donors) in the Brazilian Amazon, 1:2450 (163 of 399,326 donors) and 1:3239 (95 of 307,740 donors) at the Hong Kong Red Cross Blood Transfusion Service and Shenzhen Blood Center of South China, 1:19,130 (23 to 4.4 million donors) in the Netherlands, 1:14,903 (34 of 506,689 donors) in Spain, at least 1:2200 (548 of 1,205,796 donors) in a multicenter investigation in China, and 1:5045 (298 of 1,503,484 donors) in a worldwide, multicenter investigation . A recent survey conducted by the National Institute of Diagnostics and Vaccine Development in Infectious Diseases of China showed that the incidence of OBI in blood donors in South China was 1:631 (61 of 38,499 donors), and more than one‐half (34 of 61 donors) of the OBI blood samples harbored major hydrophilic region (MHR) mutations, which are associated with failure to detect HBsAg .…”
mentioning
confidence: 99%